2009
DOI: 10.1021/ic900738m
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Tungsten Trioxide Hydrates (TTHs) Synthesis - Is There Anything New?

Abstract: We report a very simple precipitation route to prepare a layered perovskite-type structure, tungsten trioxide hydrate (TTH), with the nominal chemical formula of WO(3) x 1.3 H(2)O (identical with 1/2H(2)W(2)O(7) x 1.6 H(2)O), using aqueous Na(2)WO(4) and SrCl(2). Our investigation shows that the concentration of HCl used to dissolve the SrCl(2) plays a crucial role in the stabilization of different structure types of layered TTHs. Highly acidic SrCl(2) (dissolved in 9 M HCl) solution yields an orthorhombic lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…The importance of WO 3 · n H 2 O stems from the fact that generally in liquid‐phase synthesis routes, WO 3 hydrates are first produced and subsequently annealed to obtain the desired crystal phase of WO x . The reports on these hydrates can be traced back to almost a century ago,18, 19 with the four most studied classes presented as WO 3 ·2 H 2 O (dihydrate), WO 3 ·H 2 O (mono­hydrate), WO 3 ·0.5 H 2 O (hemihydrate), and WO 3 ·0.33 H 2 O. The crystal structures of WO 3 hydrates are highly dependent on their water content 19.…”
Section: Fundamental Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of WO 3 · n H 2 O stems from the fact that generally in liquid‐phase synthesis routes, WO 3 hydrates are first produced and subsequently annealed to obtain the desired crystal phase of WO x . The reports on these hydrates can be traced back to almost a century ago,18, 19 with the four most studied classes presented as WO 3 ·2 H 2 O (dihydrate), WO 3 ·H 2 O (mono­hydrate), WO 3 ·0.5 H 2 O (hemihydrate), and WO 3 ·0.33 H 2 O. The crystal structures of WO 3 hydrates are highly dependent on their water content 19.…”
Section: Fundamental Propertiesmentioning
confidence: 99%
“…The reports on these hydrates can be traced back to almost a century ago,18, 19 with the four most studied classes presented as WO 3 ·2 H 2 O (dihydrate), WO 3 ·H 2 O (mono­hydrate), WO 3 ·0.5 H 2 O (hemihydrate), and WO 3 ·0.33 H 2 O. The crystal structures of WO 3 hydrates are highly dependent on their water content 19. WO 3 ·2 H 2 O possesses a layered structure, which is composed of WO 5 (OH) 2 single sheets in corner‐sharing mode.…”
Section: Fundamental Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the orthorhombic-WO 3 $0.33H 2 O crystal structure consists of layered stacks of WO 5 (OH 2 ) octahedra and interlayer water molecules. [44][45][46] For orthorhombic-WO 3 $0.33H 2 O, the interlayer water molecules connected the WO 5 (OH 2 ) octahedra planes through hydrogen bonds. The FTIR spectrum of sample W-0.0Ag shows vibrational bands located at 3494 and 3470 cm À1 (region-4) which are usually attributed to -OH and H 2 O stretching vibrations, while an additional sharp band due to structural water molecules View Article Online appears at 1606 cm À1 (region-3) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each tungsten in the structure is surrounded by one double‐bonded terminal oxygen O t along the direction normal to the plane, four single‐bonded bridging oxygen O b in the plane, and one coordinated water molecule via secondary bonding at the opposite position to WO short bond . WO 3 ·1.3H 2 O and WO 3 ·H 2 O were also claimed to be layered structured . WO 3 ·H 2 O is formed by the topotactic loss of the interlayer water molecules on dehydration of the dihydrate.…”
Section: Approaches To 2d Intercalation Chemistrymentioning
confidence: 99%